Instability of retroviral vectors with HIV-1-specific RT aptamers due to cryptic splice sites in the U6 promoter - Braun, Stephen E (BioMed Central, 2007)
BACKGROUND: Internal polymerase III promoters in retroviral vectors have been used extensively to express short RNA sequences, such as ribozymes, RNA aptamers or short interfering RNA inhibitors, in various positions and orientations. However, the stability of these promoters in the reverse orientation has not been rigorously evaluated. RESULTS: A series of retroviral vectors was generated carrying the U6+1 promoter with 3 different HIV-1 RT-specific RNA aptamers and one control aptamer, all in the reverse orientation. After shuttle packaging, the CD4(+ )cell line CEMx174 was transduced with each vector, selected for expression of GFP, and challenged with HIV-1. We did not observe inhibition of HIV-1 replication in these transduced populations. PCR amplification of the U6+1 promoter-RNA aptamer inhibitor cassette from transduced CEMx174 cells and RT-PCR amplification from transfected Phoenix (amphotropic) packaging cells showed two distinct products: a full-length product of the expected size as well as a truncated product. The sequence of the full-length PCR product was identical to the predicted amplicon sequence. However, sequencing of the truncated product revealed a 139 bp deletion in the U6 promoter. This deletion decreased transcriptional activity of the U6 promoter. Analysis of the deleted sequences from the U6 promoter in the antisense direction indicated consensus splice donor, splice acceptor and branch point sequences. CONCLUSION: The existence of a cryptic splice site in the U6 promoter when expressed in a retroviral vector in the reverse orientation generates deletions during packaging and may limit the utility of this promoter for expression of small RNA inhibitors.